O-004 Endovascular therapy in large infarct core strokes: a subgroup analysis of the trevo registry. (22nd July 2018) - Nogueira, R; Liebskind, D; Veznedaroglu, E; Budzik, R; Gupta, R
Abstract : Introduction: The recent thrombectomy trials were largely limited to patients with small strokes on presentation. We evaluate the outcomes of thrombectomy in patients with large strokes on baseline imaging. Methods: Patients were derived from a large prospective multicenter international stent-retriever registry (n=2, 010). Baseline NCCT-ASPECTS and Infarct Core Volumes on CT perfusion (rCBF<30%) were independently adjudicated by a Core Lab. Baseline and outcome variables were compared according to ASPECTS 0–5 vs 6–10 on baseline NCCT as well as to large age-adjusted cores (<70 mL if age ≤70 years; >50 mL if age <70–80 years; <30 mL if age <80 years) vs not on baseline CTP. The primary and secondary efficacy endpoint were the rates of 90-day mRS 0–2 and mTICI 2b–3, respectively. Safety endpoints included sICH and 90-day mortality. Results: A total of 1, 193 patients were included in the ASPECTS analysis. As compared with patients with higher baseline ASPECTS, low baseline ASPECTS (0–4, n=78; 5, n=78) patients were generally younger, had higher stroke severity, and tend to have less comorbidities and undergo thrombectomy at later times (table 1a). TICI-3 reperfusion was higher in the higher-ASPECTS group but other reperfusion outcomes were similar. Safety was comparable. 90-day mRS 0–2 rates were significantly higher in the high-ASPECTS group (p<0.001); however, 41.8% of ASPECTS 0–5 patients were independent at 90 days and safety outcomes were comparable (table 1b). Analysis according to large age-adjusted core (n=86) vs not yielded similarly encouraging results (table 2a–b). Conclusion: Patients with large baseline cores may still achieve favorable outcomes with endovascular treatment. Disclosures: R. Nogueira: 2; C; Stryker Neurovascular. D. Liebskind: 2; C; Stryker Neurovascular. E. Veznedaroglu: 2; C; Stryker Neurovascular. R. Budzik: 2; C; Stryker Neurovascular. R. Gupta: 2; C; Stryker Neurovascular.